Decreased TGF-β Expression in PCOS-IR Rat Models after a Low-Carbohydrate High-Protein Diet - Ermawati (Journal of Health Science Community, 2024)
Transforming growth factor β (TGF-β) is commonly associated with PCOS (Polycystic Ovary Syndrome) conditions and Insulin Resistance (IR). This is because TGF-β is a powerful regulator for the proliferation and differentiation of many cell types by directing the expression of hundreds of target genes including insulin. Hence, this research aims to identify the expression of TGF-β in PCOS-IR Rat Models after a low-carbohydrate, high-protein diet. The research design applied was the true experimental design. The selected population was female white rats (Rattus norvegicus), 3 months old, and weighing 100-200 grams. Modeling of PCOS with insulin resistance was carried out by injecting testosterone propionate hormones at a dose of 100 mg/kg BW for 28 days. On the last day after injection, a vaginal swab was taken to identify diestrus conditions. In the ANOVA test results, it was obtained p-value = 0.172, indicating that there is no significant difference in the mean value of TGF-β expression. It is said to be insignificant since the p-value <0.05. This research concludes that there is no significant difference in the mean value of TGF-β expression. Based on the mean value of TGF-β expression, it shows that the treatment group tends to have a lower mean value compared to the control group